Mobile phone use and risk of glioma in adults: case-control study. Issue 7546 (20th January 2006) - Hepworth, Sarah J; Schoemaker, Minouk J; Muir, Kenneth R; Swerdlow, Anthony J; van Tongeren, Martie J A; McKinney, Patricia A
Abstract: Objective To investigate the risk of glioma in adults in relation to mobile phone use. Design Population based case-control study with collection of personal interview data. Setting Five areas of the United Kingdom. Participants 966 people aged 18 to 69 years diagnosed with a glioma from 1 December 2000 to 29 February 2004 and 1716 controls randomly selected from general practitioner lists. Main outcome measures Odds ratios for risk of glioma in relation to mobile phone use. Results The overall odds ratio for regular phone use was 0.94 (95% confidence interval 0.78 to 1.13). There was no relation for risk of glioma and time since first use, lifetime years of use, and cumulative number of calls and hours of use. A significant excess risk for reported phone use ipsilateral to the tumour (1.24, 1.02 to 1.52) was paralleled by a significant reduction in risk (0.75, 0.61 to 0.93) for contralateral use. Conclusions Use of a mobile phone, either in the short or medium term, is not associated with an increased risk of glioma. This is consistent with most but not all published studies. The complementary positive and negative risks associated with ipsilateral and contralateral use of the phone in relation to the side of the tumour might be due to recall bias.